Smart Hydroponic System - Zailaini, Zul Najmi; Md.amin, Zulkarnain; Mohammad Fauzi, Muhammad Ezzat Syahmie; Abu Bakar, Ahmad Adnan (Multidisciplinary Applied Research and Innovation, 2022)
Abstract : In today's world, soil deficiency causes a reduction in plant productivity and health due to the frequent use of chemical pesticides and a shortage of water. Hydroponics is the process of growing plants without the use of soil. We developed a technology that can grow plants without the use of soil in this research. The goal of this project is to create a working prototype of a hydroponics controller. A shield for the Arduino Mega-2560 will be designed as part of the project. A sensor, such as a temperature sensor, a water sensor, or a light sensor, can maintain and manage a system parameter. An automated system has the advantage of operating the pumps and timers for you, ensuring that the plant receives the nutrients it requires at all times and increasing the plant's success rate. The advantage of the controller is that the plants can be watered even if the user is not at home. Hydroponics is a technique of plant growing without soil using mineral nutrient solutions or water. It is also called “Controlled Environmental Agriculture” (CEA). Hydroponics, a water culture, now used in both research and commercial field. For fast-growing horticultural crops like strawberries, lettuce, tomatoes, and carnations, certain countries have successfully applied this strategy. Scientists observed that, in comparison to soil-based growth, hydroponic plant systems only require a small amount of inorganic ingredients in addition to water, oxygen, and light to grow the plant.